Willingness to participate in direct load control: The role of consumer distrust. (1st March 2017) - Stenner, Karen; Frederiks, Elisha R.; Hobman, Elizabeth V.; Cook, Stephanie
Highlights: Consumers use trust and distrust as decision heuristics to help guide behaviour. Distrust may reduce willingness to participate in direct load control programs. Efforts by a utility to regain customer trust may increase willingness to participate. Using mixed methods, we conduct a survey-experiment to examine these issues. Abstract: Addressing the challenge of peak demand is a major priority for energy utilities, regulators and policymakers worldwide. Against this backdrop, residential demand management solutions – including direct load control technology that allows utilities to turn specific household appliances on and off during peak periods – are becoming increasingly important. While such technology has been available for decades, acceptance and adoption among residential consumers has not always kept pace. Why is this so? Drawing on key principles from psychology and behavioural economics, we propose that consumer distrust can play a significant role in the uptake of demand management solutions. As part of a large field study, a survey-experiment was conducted to investigate householders' willingness to participate in a direct load control program offered by an Australian energy company. To specifically examine the relationship between self-reported distrust and willingness to participate, and how this relationship might be influenced, the survey included an unobtrusive experimental manipulation: a simple two-sentence message designed to rebuild consumer trust and confidence in the utility was conveyed to a randomly-selected subsample of participants. Results suggested that participants' self-professed distrust in the utility was associated with significantly lower willingness to register for the DLC program. This unwillingness was modestly reduced for those participants who received the trust-restoring message upfront. Together, these results suggest that distrust may serve as an important decision-making heuristic used by consumers when choosing whether to accept new demand management technology and services. Implications for future research and practice are discussed.